Comparing Traffic Performances Of Turboroundabouts And Conventional Roundabout (Case Study) - Izadi, Amir; Mirzaiyan, Danial; Rashidi, Abbas; Hosseini, Mohsen (The Turkish Online Journal of Design Art and Communication, 2016)
Research conducted by Yperman and Immers in 2003 shows that the new geometry of these roundabouts, limits ''wavelike-movements'' and by convincing the driver to use a maximum of 2 lines, provides increasing capacity from 12 % to 20 % in the rotation (island) [4]. According to studies done on a especial case, by Lenin A.Bulla and William Castro, the results showed 7 % increase of capacity in Turbo-roundabouts in comparison with the typically roundabouts[5].In terms of capacity, the results are not consensual. Some authors, using simplified approaches, concluded that turbo-roundabouts offer better capacity than conventional roundabouts of similar size. The application of a new lanebased method reveals that only in very specific scenarios that are uncommon in real-world networks can a standard turbo-roundabout be expected to provide more capacity than the equivalent two-lane roundabout.
Keywords: traffic; turbo-roundabout; conventional roundabout